Local Anesthesia in Neonatal Lumbar Puncture - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The success rate of lumbar punctures was compared in neonates allocated prospectively to 0.2 to 0.5 mL of 1% lidocaine anesthesia (n=48) or a control group (n=52) in a study at the Albany Medical College of Union University, Albany, New York.